1997
DOI: 10.1590/s0004-282x1997000200005
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of cell-mediated immune response in children with febrile seizures

Abstract: -The aim of the present investigation was to study the distribution of T-cell subsets in peripheral blood defined by monoclonal antibodies and by the lymphocyte proliferative response to phytohemagglutinin (PH A) in 30 children with febrile seizures and in 14 age-matched control subjects. Frequent respiratory, urinary and dermatologic infections were observed in 22 patients. The immunologic parameters showed that 64% of the patients presented an increased number of CD8+ cells and a low helper/suppressor ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
2
0
1
Order By: Relevance
“…The results of lymphocyte proliferation in response to PHA stimulus showed a significant impairment of cell-mediated immunity when lymphocytes of patients were stimulated in vitro with the mitogen, in the presence of their own plasma, as detected by the low blastogenic index. These results as well as the reports obtained in other pathologies such as, febrile seizures 36 and infectious diseases 23,37 are compatible with the presence of inhibitory factors in patient plasma. The nature of these inhibitory factors has not been clarified yet, but some evidence indicate that antibodies, immune complexes, serum protein as alpha2-macroglobulin and parasite antigens may Naspitz, 1992 [25].…”
Section: Resultssupporting
confidence: 90%
“…The results of lymphocyte proliferation in response to PHA stimulus showed a significant impairment of cell-mediated immunity when lymphocytes of patients were stimulated in vitro with the mitogen, in the presence of their own plasma, as detected by the low blastogenic index. These results as well as the reports obtained in other pathologies such as, febrile seizures 36 and infectious diseases 23,37 are compatible with the presence of inhibitory factors in patient plasma. The nature of these inhibitory factors has not been clarified yet, but some evidence indicate that antibodies, immune complexes, serum protein as alpha2-macroglobulin and parasite antigens may Naspitz, 1992 [25].…”
Section: Resultssupporting
confidence: 90%
“…Various other immunological parameters are also different in patients with FS. In a study by Montelli et al [8], an increase in CD8 + count, a low helper/supresor T lymphocytes ratio and a defective proliferative response to phytohemagglutinin in lymphocytes were detected in patients with FS. Based on literature data, some authors suggested that the balance between proinflammatory and antiinflammatory cytokines might have a role in the pathogenesis of FS [4].…”
Section: Introductionmentioning
confidence: 95%
“…IgA ve febril nöbetin temporal lob epilepsiye dönüşüm riski Liimatainen S. ve ark. tarafından %8.8 olarak bulunmuştur (26). Hafez M ve ark.…”
Section: Gereç Ve Yöntemunclassified